Evaluasi Penyimpanan Obat di Gudang Rumah Sakit Umum Daerah Lanto, Jeneponto - Debby Ayu Cahyani; Rusli Rusli (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Storage is an activity of storing and maintaining by placing the received pharmaceutical supplies in a place that is considered safe from theft and physical disturbance that can damage the quality of the drug. The purpose of this study was to determine the drug storage system at the Dearh Lanto Dg Pasewang General Hospital Pharmacy Warehouse which includes spatial arrangements, storage methods, stock card recording and drug quality observation. This is done by direct observation The research conducted is descriptive in nature, the data collection method in this study is by direct observation. The data management and analysis techniques that the authors used in this study included reducing the checklists that had been obtained. Based on the results of research conducted at the Pharmacy Warehouse of the Lanto Dg Pasewang Hospital, in general, the drug storage system was 93.22% in the good category. The assessment includes the physical condition of the warehouse with a value of 90.47% in the good category. How to store drugs with a value of 93.33%. Stock card recording with a percentage value of 100% is in the good category. Drug quality monitoring with a percentage value of 100% is in the good category, so that the medicines stored in the Warehouse of the Regional General Hospital Lanto Dg Pasewang Jeneponto are in good condition and the quality of the drugs is maintained.